Graduate programs in engineering and computer science 2004 (Princeton, N.J., 2003)
A compact, easy-to-use guide to graduate and professional programs in the U.S. Readers can compare hundreds of programs in engineering and computer science.
Keywords: Engineering,Computer science,Universities and colleges; Study and teaching (Graduate),Directories,Study and teaching (Graduate),Directories,Directories; United States,United States, United States